Tinjauan Kasus Kegawatdaruratan Maternal Dan Neonatal - Sefita Aryuti Nirmala; R. Tina Dewi Judistiani; Sri Astuti; Wulan Tanti Aprianti (SEAJOM: The Southeast Asia Journal of Midwifery, 2018)
The maternal mortality (AKI) and the neonatal mortality (AKN) in Kabupaten Sumedang is caused by the maternal urgency and neonatal. The maternal urgency is a dangerous phenomena that can be a life-threatening caused by the problems of pregnancy, labor, and postpartum. It is the phenomena that threatens the life of newborn babies in the range of 0-28 days old. This study aimed to investigate the maternal and neonatal urgency in Puskesmas PONED Tanjungsari in 2015. Descriptive method with cross sectional approachment was used in this study. The data was retrospectively gained from the medical record of the patients that experienced maternal and neonatal urgency in Puskesmas PONED Tanjungsari Kabupaten Sumedang in 2015. The cases of maternal urgency that frequently happened in Puskesmas Tanjungsari was premature rupture of membranes that reached 28 cases or 37,8%. Meanwhile, in 2015, there was no neonatal urgency happened and recorded in Puskesmas PONED Tanjungsari. The characteristics of maternal age that experienced the maternal urgency was about 20-35 years ord with 51 cases happened or 68,9%. The number of live birth in range of 2-3 reached 37 cases or 50%. The referal cases with a healthy condition reached 72 cases or 97,3% and for them who got complicated cases reached 2 cases or 2,7%. The cases of maternal and neonatal urgency that happened in Puskesmas Tanjungsari mostly caused by the premature rupture of membranes with the characteristics of maternal age about 20-35 years old and the number of live birth in range of 2-3. Puskesmas Tanjungsari has followed the clinic procedure before referring the patients to the nearest PONEK hospital by doing stabilization to the patients. Moreover, the condition of the patients reffered to the nearest PONEK hospital were mostly in a good and health condition.